PENGARUH PENYAJIAN LAPORAN KEUANGAN DAERAH, AKSESIBILITAS LAPORAN KEUANGAN DAERAH DAN TINGKAT PENGUNGKAPAN SUKARELA LAPORAN KEUANGAN DAERAH TERHADAP AKUNTABILITAS PENGELOLAAN KEUANGAN DAERAH (Studi Empiris Pada SKPD Provinsi Riau) - Putri, Firstcilia Eldy; Anisma, Yuneita; ', Al Azhar A (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aimes to examine the effect of the presenting of regional financial report, accessibility of regional financial report and level of regional financial report voluntary explanation to accountability of financial. The population of research is SKPD in Provincial Goverment of Riau. This study is using primer data. Data analysis for hypothesis test was done with Statistical Product and Service Solutions (SPSS). There are 93 questionnaires were sent, but only 87 questionnaires are returned. The variables were examined presenting of regional financial report, accessibility of regional financial report and level of regional financial report voluntary explanation to accountability of financial. The results of this research showed presenting of regional financial report has an effect to the accountability of financial with 0,004 significance, accessibility of regional financial report has an effect to the accountability of financial with 0,025 significance and level of regional financial report voluntary explanationhas an effect to the accountability of financial with 0,000 significance. The results of this research also showed that coefficient R square is 56,2%. Each independent variables, gives the strong influence to dependent variable, it means independents variables could explain dependent variable well. While the remaining influenced by other variables not included in the regression models were not included in this study. All variables also have strong relation with variable dependents in this research.Keywords: presenting, accessibility, level of voluntary explanation, accountability